(untitled) (Research, Society and Development, 2022)
Pod beans (Phaseolus vulgaris L.) are among the most consumed vegetables in Brazil. It differs from the common bean cultivated for grain production, mainly by the lack of fibrosity in the fruit that allows its use in human food. As for the density of plants to be used, there is no concession based on the literature which is the best parameter to use. The objective of this work was to evaluate the productivity and yield as a function of different plant densities of the short bean macaroni grown in an organic system in a protected environment. The experiment was carried out in a completely randomized design (DIC). Five treatments were tested with 16 replications each: T1 = one plant/pot; T2 = two plants/pot; T3 = three plants/pot; T4 = four plants/pot and T5 = five plants/pot. The variables evaluated were: Total Production of Pods; Weight of Defective Pods; Weight of Trading Pods and Size of Trading Pods. Based on the results obtained, no significant differences were detected for the variables evaluated. Analyzing the general averages, treatment 2 was the one that resulted in the highest productivity with 24.76 t ha-1 and with 75% yield of good pods, suitable for commercialization. Pod bean cultivation is viable under the conditions, even at higher densities, with the potential to be an alternative crop rotation with potential profit for the rural producer.